Ethanol consumption during gestation promotes placental alterations in IGF-1 deficient mouse placentas [version 3; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Mario Bermúdez De León; Diego Rodríguez-Mendoza; Carolina Zertuche-Mery; Inma Castilla-Cortázar; Oscar R Fajardo-Ramírez; Fabiola Castorena-Torres; Marcela Galindo-Rangel; Patricio Gómez-Álvarez; Irene Martín-Estal; Andrea Leal López (F1000Research)
Background During pregnancy, the placenta is an extremely important organ as it secretes its own hormones, e.g. insulin-like growth factor 1 (IGF-1), to ensure proper intrauterine fetal growth and development. Ethanol, an addictive and widely used drug, has numerous adverse effects during pregnancy, including fetal growth restriction (FGR). To date, the molecular mechanisms by which ethanol triggers its toxic effects during pregnancy, particularly in the placenta, are not entirely known. For this reason, a murine model of partial IGF-1 deficiency was used to determine ethanol alterations in placental morphology and aspartyl/asparaginyl β-hydroxylase (AAH) expression. Methods Wild type (WT, Igf1 +/+) and heterozygous (HZ, Igf1 +/-) female mice were given 10% ethanol in water during 14 days as an acclimation period and throughout pregnancy. WT and HZ female mice given water were used as controls. At gestational day 19, pregnant dams were sacrificed, placentas were collected and genotyped for subsequent studies. Results IGF-1 deficiency and ethanol consumption during pregnancy altered placental morphology, and decreased placental efficiency and AAH expression in placentas from all genotypes. No differences were found in Igf1, Igf2, Igf1r and Igf2r mRNA expression in placentas from all groups. Conclusions IGF-1 deficiency and ethanol consumption throughout gestation altered placental development, suggesting the crucial role of IGF-1 in the establishment of an adequate intrauterine environment that allows fetal growth. However, more studies are needed to study the precise mechanism to stablish the relation between both insults.